Aktivitas Antioksidan Ekstrak Daun, Bunga, dan Tangkai Sirih Hutan (Piper aduncum L.) - Mariani, Ria; Perdana, Farid; Widiana, Revi (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2023)
Abstract: Forest Betel (Piper aduncum L.) belongs to the genus Piper. Many researches on antioxidants of various genera of Piper have been carried out such as Piper crocatum and Piper betle, but research on antioxidants in forest betel is still very limited. Natural antioxidants can be used to reduce free radicals in an effort to prevent degenerative diseases. This study aims to determine the antioxidant activity of flowers, leaves and stalks of forest betel and the group of compounds responsible for the antioxidant activity. Antioxidant activity was tested using the DPPH method (2,2 diphenyl-1-picrylhydrazyl) with UV-Vis spectrophotometry and thin layer chromatography (TLC). The antioxidant activity test results using UV-Vis spectrophotometry showed that forest betel leaf extract had 47.252 µg/ml as an IC50 value, forest betel flower extract had 49,756 µg /ml as an IC50 value and forest betel stalk extract had 48.674 µg/ml as an IC50 value.. While vitamin C as a comparison has 5.223 µg/ml as an IC50 value. From the TLC results showed that the compounds suspected of providing antioxidant activity in the flower and stalk extracts were flavonoid compounds because they had the same Rf values, which 0.35; 0.53; 0.66 on the plates that had been sprayed with DPPH and sitroborate. Extracts of leaves, flowers and stalks of forest betel have antioxidant activity with IC50 of 47.252; 49.756 and 48.674 µg/ml respectively and suspected the presence of flavonoid compounds that are responsible for the antioxidant activities of flower and stalk extract.